Say cheese!—equestrian helmet use in publication photos of horse organisations. (7th October 2012) - Jennissen, C; Waheed, S; Harland, K; Denning, G
Abstract : Background: Equestrian helmets are effective in preventing head injuries, but use remains low. The media can have a great impact on injury prevention both positively and negatively by their portrayal of protective safety equipment or lack thereof. Aims/Objectives/Purpose: To determine the equestrian helmet use of individuals pictured in horse organisation promotional materials. Methods: Literature was requested from horse organisations. Photographs in the materials received were reviewed for equestrian helmet use and analysed. Results/Outcomes: 113 of 335 organisations responded and 95 sent publications. 2004 photos with 2738 people were evaluated. The highest equestrian helmet use was by children, and teen helmet use was generally portrayed more frequently than in adults. The lowest rate was in the elderly (14.6%). Helmet use was highest in photos that depicted competition-jumping (87.9%). Competition-riding and pleasure-riding helmet use was only 30.0% and 34.5%, respectively. No one who was pictured while working on, with or while on a horse was shown with an equestrian helmet; nor was anyone in a parade. Adults riding with children did have a higher rate of wearing an equestrian helmet than adults who were pleasure-riding in general (44.2% vs 23.2%). Significance/Contribution to the Field: Photographs in horse organisation literature often show people not wearing helmets during equine-related activities. Horse organszations have the ability to define equestrian helmet use as normative behaviour by always portraying people with helmets in their published materials. Developing an equestrian safety culture of routine helmet use should decrease the number of serious head injuries experienced by horse enthusiasts.